Cultural adaptation and validity of the Malay version of the brief psychiatric rating scale (BPRS-M) among patients with schizophrenia in a psychiatric clinic - Yee, A.; Ng, B.S.; Hashim, H.M.H.; Danaee, M.; Loh, H.H. (BioMed Central, 2017)
Background: This study evaluates the psychometric properties of the Malay version of the Brief Psychiatric Rating Scale (BPRS-M) among patients with schizophrenia in a psychiatric outpatient clinic. Methods: Ninety-nine schizophrenia outpatients were administered the Malay version of the Brief Psychiatric Rating Scale (BPRS-M), Malay version of Positive and Negative Syndrome Scale (PANSS), Malay version of Calgary Depression Scale for Schizophrenia (CDSS) and Malay version of World Health Organization Quality of Life - Brief Version (WHOQOL-BREF). Results: An exploratory factor analysis (EFA) of BPRS-M produced a seven-factor solution which accounted for 71.4% of the total variance. It exhibited fair internal consistency (Cronbach's alpha coefficient of 0.75). "Positive symptoms" and "Resistance" factors had association with unemployment and number of antipsychotics, positively correlated with PANSS but negatively correlated with WHOQOL-BREF. "Mood disturbance" factor correlated with lifetime history of suicide attempts, Malay version of CDSS and WHOQOL-BREF (psychological). Both "Negative symptoms" and "Activation" factors were associated with male, lower education, unemployment and positively correlated with Malay version of PANSS but negatively correlated with WHOQOL-BREF. Conclusions: The BPRS-M demonstrated promising psychometric properties in terms of dimensionality, reliability, and validity that generally justifies its use in routine clinical practice in Malaysia.